PENGARUH PEMANFAATAN ARTIFICIAL INTELLIGENCE DAN TINGKAT LITERASI DIGITAL TERHADAP KEMAMPUAN BERPIKIR KRITIS MAHASISWA PRODI PENDIDIKAN EKONOMI FIS UPMI BALI - Kulla, Linda; Ni Luh Putu Yesy Anggreni; Putu Siti Firmani (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2025)
Abstract This study aims to analyze the extent to which the use of Artificial Intelligence (AI) and the level of digital literacy influence students’ critical thinking skills. The research subjects were students of the Economic Education Study Program at the Faculty of Social Sciences, Universitas PGRI Mahadewa Indonesia. A quantitative approach was employed, with data collected through questionnaires distributed to 50 respondents. The data analysis technique used was multiple linear regression. The findings revealed that individually, AI and digital literacy did not have a significant influence on critical thinking skills. However, when considered together, both variables showed a significant effect. The coefficient of determination value of 0.748 indicates that 74.8% of the variability in critical thinking skills is explained by these two variables. Therefore, the study concludes that the combined utilization of technology and digital literacy skills plays an important role in enhancing students’ critical thinking abilities. Keywords: Artificial Intelligence, digital literacy, critical thinking.